Isolation of Clostridium perfringens and Clostridioides difficile in diarrheic and nondiarrheic cats - Silva, Rodrigo Otávio Silveira; Ribeiro, Marcio Garcia [UNESP]; de Paula, Carolina Lechinski [UNESP]; Pires, Isadora Honorato; Oliveira Junior, Carlos Augusto; Diniz, Amanda Nadia; de Araújo Nunes, Talita Augusto; Lobato, Francisco Carlos Faria (Elsevier, 2020)
The occurrence and characteristics of Clostridioides (previously Clostridium) difficile and Clostridium perfringens in the feces of diarrheic and non-diarrheic cats was investigated. Apparently healthy animals were more likely to be positive for C. perfringens type A (p = 0.009). Two isolates (0.7%), one each from a diarrheic and an apparently healthy cat, were positive for the enterotoxin-encoding gene but negative for the NetF-encoding gene. Six toxigenic C. difficile isolates were isolated, all RT106 and ST42, which is commonly reported in humans with C. difficile infection.
Keywords: Colitis; Diarrhea; Feline